CONTENIDOS DIGITALES Y SU IMPORTANCIA EN EL APRENDIZAJE DE LOS ESTUDIANTES DE COMUNICACIÓN SOCIAL DE LA UTB EXTENSIÓN QUEVEDO, AÑO 2022 - Mosquera Posligua, Saira Liseth (2022)
The objective of this research work was to analyze the importance of digital content in the learning of social communication students at the Technical University of Babahoyo Extension Quevedo. Where the following hypothesis is proposed: Digital content has a high level of importance in the learning of social communication students of the UTB Extension Quevedo. To determine the stated objective, a type of descriptive and explanatory or casual research was used where the population consisted of students from the Social Communication career at the Technical University of Babahoyo Extension Quevedo, taking a total sample of 171 students who would help us to obtain the results of our research through a survey carried out in the form of a questionnaire which contained a total of 10 questions. As main results of our investigation it was possible to determine that the students do not have the optimal and adequate knowledge, much less a totally suitable guide on the realization of digital content. There is a great lack in the field of knowledge and development of digital content since the university curriculum does not have subjects and hours of practice that help strengthen this knowledge. To solve the existing problem, it is proposed to make changes and implement subjects and hours of practice, as well as constant training for teaching staff in the use of ICTs and the teaching of everything related to the creation of digital content.